2003
DOI: 10.1037/1076-8998.8.4.282
|View full text |Cite
|
Sign up to set email alerts
|

"The very best of the millennium": Longitudinal research and the demand-control-(support) model.

Abstract: This study addressed the methodological quality of longitudinal research examining R. Karasek and T. Theorell's (1990) demand-control-(support) model and reviewed the results of the best of this research. Five criteria for evaluating methodological quality were used: type of design, length of time lags, quality of measures, method of analysis, and nonresponse analysis. These criteria were applied to 45 longitudinal studies, of which 19 (42%) obtained acceptable scores on all criteria. These high-quality studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
762
9
20

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 898 publications
(856 citation statements)
references
References 73 publications
65
762
9
20
Order By: Relevance
“…In future research pleasure and arousal have to be conceived as respectively affective and cognitive concepts. Regarding dominance, many researches showed the importance of feelings of control related to behaviour (Seligman, 1975;Frijda, 1988;Gaillard, 2003) and health (Johnson & Hall, 1988;Furda et al, 1994;Warr, 1994;Gaillard, 2003;De Lange et al, 2003;De Lange et al, 2004). These aspects were also mentioned by Karasek and related to workload and stress in his model together with Theorell in 1990(in Gaillard, 2003.…”
Section: Resultsmentioning
confidence: 95%
“…In future research pleasure and arousal have to be conceived as respectively affective and cognitive concepts. Regarding dominance, many researches showed the importance of feelings of control related to behaviour (Seligman, 1975;Frijda, 1988;Gaillard, 2003) and health (Johnson & Hall, 1988;Furda et al, 1994;Warr, 1994;Gaillard, 2003;De Lange et al, 2003;De Lange et al, 2004). These aspects were also mentioned by Karasek and related to workload and stress in his model together with Theorell in 1990(in Gaillard, 2003.…”
Section: Resultsmentioning
confidence: 95%
“…None of the tested JDCS interaction effects were significant predicators within the given sample of teachers. Previous studies have observed consistent evidence of the main effects of the JDCS work characteristics (Noblet and LaMontagne 2006;Hausser et al, 2010;Luchman and Gonzales-Morales, 2013); however, evidence of their interactive nature of these variables is mixed and observably weak (van der Doef and Maes, 1999;De Lange et al, 2003).…”
Section: The Influence Of Jdcs Work Characteristicsmentioning
confidence: 99%
“…For example, research based on the Demand-Control model (Karasek & Theorell, 1990) has shown that high job demands and low levels of control at work are associated with increased strain and psychophysiological complaints (de Lange, Taris, Kompier, Houtman & Bongers, 2003;Van der Doef & Maes, 1999). In the context of the Effort Recovery Theory, increased job demands interfere with recovery processes by reducing the time available to the individual; and limited control at work can damage recovery because individuals may be required to continue expending effort at times when they require a break psychologically and physiologically.…”
Section: Control Variablesmentioning
confidence: 99%